2017
DOI: 10.1007/s11692-017-9436-5
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Perspective on Linoleic Acid Synthesis in Animals

Abstract: The diet of organisms generally provides a sufficient supply of energy and building materials for healthy growth and development, but should also contain essential nutrients. Species differ in their exogenous requirements, but it is not clear why some species are able to synthesize essential nutrients, while others are not. The unsaturated fatty acid, linoleic acid (LA; 18:2n-6) plays an important role in functions such as cell physiology, immunity, and reproduction, and is an essential nutrient in diverse org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 88 publications
1
59
0
Order By: Relevance
“…In the present study, among dietary nucleotides, dietary GMP, UMP and CMP significantly increased hepatic linoleic acid (LA, 18:2n-6) and α-linolenic acid (LNA, 18:3n-3) contents (Table 8). It has been known that most of the animals are not able to synthesize LA de novo from oleic acid (OA) and synthesis of LNA from LA due to lack of ∆12 (or ω6) and ∆15 (or ω3) desaturates, and thus required a dietary sources of those fatty acids (Malcicka, Visser, & Ellers, 2018;Venegas-Calerón, Sayanova, & Napier, 2010). Moreover, the fatty acid composition of liver and muscle in rainbow trout is well known to be influenced by the composition of dietary fatty acids (Caballero et al, 2002;Fonseca-Madrigal, Karalazos, Campbell, Bell, & Tocher, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, among dietary nucleotides, dietary GMP, UMP and CMP significantly increased hepatic linoleic acid (LA, 18:2n-6) and α-linolenic acid (LNA, 18:3n-3) contents (Table 8). It has been known that most of the animals are not able to synthesize LA de novo from oleic acid (OA) and synthesis of LNA from LA due to lack of ∆12 (or ω6) and ∆15 (or ω3) desaturates, and thus required a dietary sources of those fatty acids (Malcicka, Visser, & Ellers, 2018;Venegas-Calerón, Sayanova, & Napier, 2010). Moreover, the fatty acid composition of liver and muscle in rainbow trout is well known to be influenced by the composition of dietary fatty acids (Caballero et al, 2002;Fonseca-Madrigal, Karalazos, Campbell, Bell, & Tocher, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…D and N8 had the highest linolenic acid (64.23%) and linolenic acid (2.51%) among all proso millet cultivars, respectively. Linolenic acid and linolenic acids are essential fatty acid and must be supplied via the diet (Kim, Nam, Kim, Hayes, & Lee, 2014;Malcicka, Visser, & Ellers, 2017). It is reported that linolenic acid has many benefits for human health, such as cardiovascular-protective, anti-cancer, neuroprotective, and anti-inflammatory effects (Kim et al, 2014).…”
Section: Total Fat and Fatty Acid Profilementioning
confidence: 99%
“…According to the location in the endoplasmic reticulum (ER) or plastids, Δ 12 FADs are divided into microsomal (FAD2) and plastid (FAD6) enzymes. In recent years, FAD2 genes have been identified and functionally analyzed in a variety of organisms, including plants, fungi, and some other lower animals [ 1,10]. To date, the FAD2 gene has been cloned from many plant species.…”
Section: Introductionmentioning
confidence: 99%